Differential impact of eicosapentaenoic acid and docosahexaenoic acid in an animal model of Alzheimer’s disease - Méryl-Farelle Oye Mintsa Mi-mba; Meryem Lebbadi; Waël Alata; Carl Julien; Vincent Emond; Cyntia Tremblay; Samuel Fortin; Colin J. Barrow; Jean-François Bilodeau; Frédéric Calon (Journal of Lipid Research)
Dietary supplementation with n-3 polyunsaturated fatty acids improves cognitive performance in several animal models of Alzheimer's disease (AD), an effect often associated with reduced amyloid-beta and/or tau pathologies. However, it remains unclear to what extent eicosapentaenoic (EPA) provides additional benefits compared to docosahexaenoic acid (DHA). Here, male and female 3xTg-AD mice were fed for 3 months (13–16 months of age) the following diets: (1) control (no DHA/EPA), (2) DHA (1.1g/kg) and low EPA (0.4g/kg), or (3) DHA (0.9g/kg) with high EPA (9.2g/kg). The DHA and DHA + EPA diets respectively increased DHA by 19% and 8% in the frontal cortex of 3xTg-AD mice, compared to controls. Levels of EPA, which were below the detection limit after the control diet, reached 0.14% and 0.29% of total brain fatty acids after the DHA and DHA + EPA diet, respectively. DHA and DHA + EPA diets lowered brain arachidonic acid levels and the n-6:n-3 docosapentaenoic acid ratio. Brain uptake of free 14C-DHA measured through intracarotid brain perfusion, but not of 14C-EPA, was lower in 3xTg-AD than in NonTg mice. DHA and DHA + EPA diets in 3xTg-AD mice reduced cortical soluble phosphorylated tau (pS202) (−34% high-DHA, −34% DHA + EPA, P < 0.05) while increasing p21-activated kinase (+58% and +83%, P < 0.001; respectively). High EPA intake lowered insoluble phosphorylated tau (−31% vs. DHA, P < 0.05). No diet effect on amyloid-beta levels was observed. In conclusion, dietary intake of DHA and EPA leads to differential changes in brain PUFA while altering cerebral biomarkers consistent with beneficial effects against AD-like neuropathology.